Evaluate CRM Performance with CSI and Science Ap-proach Implications for Marketing Strategy Umme Saladin Magic Potatoes - Rasidin Karo Karo Sitepu; Muhammad Hafidz Azizi; Amer Abdul Aziz; Muhammad Iqbal; Satrio Rasendriya Widyadhana; Farraz Ariel Gubita; Muhammad Puja Dwi Surya (International Journal of Economics and Management Research, 2025)
This study aims to evaluate the performance of Customer Relationship Management (CRM) in MSMEs of Saladin Kentang Magic using the Customer Satisfaction Index (CSI) and Importance-Performance Analysis (IPA) approaches. A further goal is to formulate a marketing strategy based on the results of the evaluation. The study used a quantitative descriptive method with data collection techniques through questionnaires distributed to 100 respondents of Saladin Potato Magic customers. The research variables include five dimensions of CRM service quality: tangible, reliability, responsiveness, assurance, and empathy. The results of the study showed a CSI value of 76.83% which showed that customers were "satisfied" with the performance of the CRM. The IPA analysis identified priority attributes for improvement in quadrant I, namely the ease of contact through social media and the speed of response to complaints. Attributes in quadrant II that need to be maintained include product variety, product quality, and employee friendliness. The implication of this study is the need for a marketing strategy that focuses on strengthening social media management, improving the complaint handling system, and maintaining product quality as a competitive advantage for Saladin Potato Magic MSMEs.